PENGARUH TARIF, LOKASI DAN STANDARISASI PELAYANAN DALAM MENINGKATKAN KEPUASAN KONSUMEN PENGGUNA JASA PT. PRATAMA MAKMUR JAYA - Mangampu Simanullang; Lolita Gultom; Lisboy Saragi; Hendra Jonathan Sibarani (Universitas Methodist Indonesia, 2020)
This study aims to analyze whether there is an effect of tariffs, location, and service standardization in increasing customer satisfaction with a population of 34,799 transportation service users and a total sample of 100 people obtained using the Slovin formula. This study uses a quantitative approach, with data collection techniques using questionnaires and interviews. The research model uses multiple linear regression analysis. The results of the research on the partial test (t-test) showed that the variable of tariffs, location, and service standardization had a positive and significant effect on customer satisfaction, while the simultaneous test (F-test) showed that the variable rates, location, and service standardization had a positive and significant effect on customer satisfaction PT. Pratama Makmur Jaya Medan.